Conditioning white spruce (Picea glauca (Moench) Voss) transplants for overwinter storage by root pruning and wrenching - Buse, Lisa J. (Lisa Jean), 1962- (My University, 1987)
Problems associated with the establishment and early growth of outplanted white spruce (Picea glauca (Moench) Voss) led to research on conditioning white spruce transplants for overwinter frozen storage by root pruning and wrenching. The objectives of the research were: 1) to use root pruning and wrenching treatments in conjunction with potassium fertilizer treatments during the final year in the nursery to modify the morphology and physiology of white spruce transplants, 2) to monitor the effects of the treatments on the shoot and root growth response of the stock during overwinter frozen storage, and 3) to monitor the performance of both overwinter frozen stored and spring lifted stock, which had been subjected to root pruning and wrenching treatments, after outplanting. In 1984, 2+1 white spmce transplants were root pruned in three phenological stages: 1) pre-flush, 2) mid-flush and 3) post-flush, followed by root wrenching at 28-day intervals. Additional potassium fertilizer was applied at three levels (0 kg/ha, 100 kg/ha and 200 kg/ha). In 1985, 2+1 white spruce transplants were root pmned early in the season followed by 1) wrenching at 21-day intervals or 2) wrenching periodically to coincide with periods of peak root growth. Additional potassium fertilizer was applied at two levels (0 kg/ha and 75 kg/ha). In both years, 25 transplants per variate were monitored throughout the season for height and root collar diameter growth. At the end of the season, these samples were assessed for morphological quality. Bud samples were collected to assess the effects of wrenching on primordia development. Samples of the stock were fall lifted and placed into overwinter frozen storage at -2°C. Batches of stock were removed from the freezer at one month intervals during the winter and assessed for time to bud break and root growth potential after 21-days in the growth chamber. Fall lifted and overwinter stored stock was outplanted simultaneously with spring lifted stock from the same experiments. The outplanted stock was assessed for root growth potential after 21 days, survival and growth after the first and second year for the 1984 root conditioning trial and the first year for the 1985 trial. Plant moisture stress was monitored for the first three weeks after outplanting. Root conditioning modified the morphology of the stock in both years by reducing height and root collar diameter and inducing the development of a more compact fibrous root system. Early season root pruning followed by wrenching at regular intervals throughout the growing season was most effective in modifying the morphology of the stock. Root growth patterns during overwinter frozen storage were different in the two years, with a mid-season peak occurring the first year and a gradual decline occurring through the winter in the second year. Shoot growth response was similar in both years. Survival was excellent but growth was poor for the 1985 outplant. Survival and growth were excellent for the 1986 outplant. Differences between the two years can be attributed to differences in climate and handling practices rather than the treatments. The results indicate that root conditioning does not confer any significant advantage to stock outplanted in wet years and that additional potassium fertilizer does not increase survival through storage or after outplanting.
Keywords: White spruce; Roots (Botany); Seedlings Storage